PENGARUH PELAPORAN ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) TERHADAP TINGKAT UNDERPRICING PADA PERUSAHAAN IPO DI BURSA EFEK INDONESIA PERIODE 2021-2024 - Hafiz Wahyu Syahputra; Ahmad Faisol (Nusantara Hasana Journal, 2026)
This study aims to examine the effect of Environmental, Social, and Governance (ESG) reporting on the level of underpricing among firms conducting Initial Public Offerings (IPOs) on the Indonesia Stock Exchange during the 2021-2024 period. This research employs a quantitative research design. The data used in this study are cross-sectional data obtained from 102 Indonesian companies that published Annual Reports and Sustainability Reports prior to their IPOs over the 2021–2024 period. The analytical method applied is Ordinary Least Squares (OLS) regression with Huber White robust standard errors, using EViews version 13 as the statistical software. The results indicate that ESG reporting, as reflected in Sustainability Reports disclosed prior to IPOs, has a significant negative effect on the level of underpricing. In addition, the findings reveal a significant difference in underpricing between companies that disclose ESG information and those that do not disclose ESG information prior to IPOs.